The Dialectics of Democracy and Development in Africa - المغيربي أ.د محمد زاهي بشير (Dirasat in Economics and Business, 2002)
The Literature on development and democracy was occupied in the last few decades by questions on the relationship between regime type and economic development. democratization conducive to economic development? Or could it be dysfunctional to development, at least in the short run? Are development countries in general, and Africa in particular, better off seeking development with authoritarian regimes? Or is the prospect of development indifferent to the authoritarian or democratic character of regimes? This paper argues that the African situation is extremely complex because of the simultaneity of the issues of democratization and economic development. To solve this problem, it is necessary to view both values as dialectical moments amenable to a synthesis. This synthesis can be achieved through the democratization of development and the development of democracy. And that means that people become the agents of development and its goal and end at the same time. To achieve this people must have ultimate control of Public Policy.